Public economics. - Johansen, Leif (North-Holland Pub. Co.; Rand McNally, 1965)
Economic theory. Problems of economic policy, fiscal policy (international comparison), public debt, state budget and accounting, consumption, forms of taxation and their effects. Role of public administration.